Distributed software defined information centric networking. (28th September 2020) - Jmal, Rihab; Fourati, Lamia Chaari
Recently, a new trend has emerged based on combining software defined networking (SDN) and information centric networking (ICN) as a promising approach for the future internet. More serious control plane problems related to scalability, fault-tolerance and consistency may affect software defined information centric networking (SD-ICN) compared to traditional SDN environment regarding new augmented features such as content name-based communication and in-network caching. In this paper, we propose a distributed software defined information centric networking (DSD-ICN) that provides ICN features over SDN network with multiple controllers. We addressed in our design the fault-tolerant and strong consistency of the control plane which allows the transparent distribution of the content over different network domains.